2015
DOI: 10.1002/hec.3293
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Health Insurance for the Informal Sector: A Cluster Randomized Experiment in Vietnam

Abstract: Subsidized voluntary enrollment in government-run health insurance schemes is often proposed as a way of increasing coverage among informal sector workers and their families. We report the results of a cluster randomized experiment, in which 3000 households in 20 communes in Vietnam were randomly assigned at baseline to a control group or one of three treatments: an information leaflet about Vietnam's government-run scheme and the benefits of health insurance, a voucher entitling eligible household members to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…A study from Viet Nam found enrolment at baseline to be 4 per cent. Information campaigns and the offer of a subsidy only increased enrolment by 1–3.5 per cent with results suggesting that such interventions may exacerbate adverse selection (Wagstaff et al, ). There is strong evidence demonstrating that voluntary health insurance programmes for the non‐poor informal sector have extremely low uptake (Cotlear et al, ).…”
Section: Discussing and Interpreting The Resultsmentioning
confidence: 99%
“…A study from Viet Nam found enrolment at baseline to be 4 per cent. Information campaigns and the offer of a subsidy only increased enrolment by 1–3.5 per cent with results suggesting that such interventions may exacerbate adverse selection (Wagstaff et al, ). There is strong evidence demonstrating that voluntary health insurance programmes for the non‐poor informal sector have extremely low uptake (Cotlear et al, ).…”
Section: Discussing and Interpreting The Resultsmentioning
confidence: 99%
“…Two randomised experiments conducted in the Philippines (Capuno et al , ) and Vietnam (Wagstaff et al ., ) reveal that substantial premium subsidies had modest, if any, impact on insurance uptake. In Vietnam, despite affordability being reported as the main reason for not purchasing insurance, a 25% subsidy had no effect, even when combined with promotion of the benefits of insurance.…”
Section: Extending Coveragementioning
confidence: 99%
“…The MFB felt that the insurance agents slowed down the loan officers, making it difficult for them to maintain their usual schedule. The insurer noted that voluntary enrollment was low and observed potential adverse selection, 2 challenges well documented in the literature . As a result, the partners decided to make insurance enrollment mandatory starting in October 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting the global commitment to advance universal health coverage (UHC), a growing number of low‐ and middle‐income countries are implementing health system reforms to reduce financial barriers and increase access to priority health services for all citizens . One major challenge for governments and other stakeholders is how to extend coverage to informal sector workers, who typically make up the majority of the population in these countries . There is a growing body of evidence on demand for health insurance and its effects on access to health services among the informal sector .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation